Implementation Actions for Improving Air Force Command and Control Through Enhanced Agile Combat Support Planning, Execution, Monitoring, and Control Processes - Lynch, Kristin F. (RAND Corporation, 2014)
Using the architecture developed as a companion piece to this analysis, this report identifies and describes where shortfalls exist between current agile combat support (ACS) processes and the vision for integrating enhanced ACS processes into Air Force command and control (C2). It evaluates C2 nodes at each echelon of responsibility and across operational phases and suggests mitigation strategies needed to facilitate an efficient and effective global C2 network.